Predictors of receiving care and folic acid supplementation prior to pregnancy: a large cross-sectional study in Shiraz, Iran - Niloufar Izaddoost; Leila Amiri-Farahani; Fatemeh Sajjadian; Sally Pezaro (BMC Pregnancy and Childbirth)
Abstract Background and aim Preconceptional care aims to improve health and is influenced by various factors including health literacy. Considering the importance and necessity of high quality preconceptional care, this study aimed to determine the predictors of receiving care and folic acid supplementation prior to pregnancy. Methods This cross-sectional study included 693 participants with pregnancies of less than 14 weeks gestation referred to health centers and gynecologists in Shiraz city, Iran. Multi-stage sampling occurred from May 2021 to February 2022 in 18 comprehensive urban health centers and 20 gynecology offices via the proportional allocation method. Data was collected using a questionnaire consisting of 3 parts: 1) individual and fertility characteristics, 2) information related to the components of preconceptional care and 3) health literacy. This was completed by individual participants who self-reported their responses. Results Examining the frequency of the variables related to individual characteristics revealed that the mean age of participants in the study was 30.32 with a standard deviation of 5.29 years and more than half (59.3%) had a university level education. The receipt of pre-conceptual care was found to have a statistically significant relationship with the following: level of education, employment status, length of marriage, number of pregnancies, week of pregnancy and whether it was planned or not, along with health literacy (P < 0.05). Folic acid supplementation was found to have a statistically significant relationship with the following: level of education, financial status of the family, length of marriage, number of pregnancies and current pregnancy status (P < 0.05). In examining the predictive effect of individual variables and health literacy in the logistic regression model with the outcome of receiving preconceptional care and folic acid supplementation, length of marriage, health literacy, occupational status, and pregnancy planning status variables remained in the model following analysis. Conclusion Several factors had a statistically significant relationship with receiving pre-conceptual care and folic acid supplementation. In order to improve pre-conceptual care and increase folic acid supplementation, special attention must be paid to improving health literacy, increasing levels of education and reducing unplanned pregnancies.